Apuntes introductorios a la pretensión de nulidad de negocio jurídico desde la perspectiva civil: Análisis crítico de la posición del Quinto Pleno Casatorio Civil respecto de la impugnación de negocios colegiales asociativos - Campos García, Héctor Augusto (Pontificia Universidad Católica del Perú, 2014)
In August 2014, the Peruvian Supreme Courten acted  the  Fifth  Civil  Cassation Plenary, which establishes that any challenging madeto an associative agreement must be realized through the procedure referred to in the article92 of the Peruvian Civil Code. The comments and criticisms to this decision have not beenfew, considering the complexity of the theme discussed in the aforementioned decision.In this context, with the present article the author realizes a thorough critique of such Cassation Plenary. Based on the analysis of civil and procedural legal concepts, he reaches a conclusion: That the plenary decision, besides of having multiple legal errors, won't accomplish its purpose.

En agosto de 2014, la Corte Suprema promulgó el Quinto Pleno Casatorio Civil, en elque dispone que todo cuestionamiento a un acuerdo asociativo deba realizarse mediantela impugnación contemplada en el artículo 92del Código Civil. Los comentarios y las críticas a esta decisión no han sido pocas, tomandoen cuenta la complejidad del tema discutido.En ese contexto, mediante el presente artículo, el autor realiza una crítica completa sobre el Pleno Casatorio. Basándose en un análisis de conceptos jurídicos civiles y procesales, llega a una conclusión: La decisión plenaria, además de tener múltiples errores jurídicos, no logra finalmente lo que se buscaba con ella.
Introductory notes for the application for a declaration of invalidity of a legal transaction from the civil perspective: Critical analysis of the position of the Fifth Civil Cassation Plenary regarding the challenging of collegiate associative transactio
Keywords: Law; Peruvian Supreme Court; Civil Cassation Plenary; Challenging Of Associative Agreements; Invalidity Of Legal Transaction; Corte suprema del perú; Pleno casatorio civil; Impugnación de acuerdos asociativos; Nulidad de negocio jurídico; https://purl.org/pe-repo/ocde/ford#5.05.01